Analysis Strategic of Ticket Purchase at Traveloka in Pangkalan Kerinci City Communities - Ermansyah, Ermansyah (MUI Kota Pekanbaru, 2023)
The study is aimed at determining the influence of Trust, Customer Review, and Customer Rating on Buying Interest. The population of the study is a community of Kerinci Base City and the sampling method used in this study is non-probability sample. Primary and secondary data are used for analysis. The analysis was done with double linear regression and SPSS 25 program. The results of the research show that the Trust, Customer Review, and Customer Rating variables have a significant influence on Buy Interest in part, while the f test shows that the trust, customer review, and customer rating variables simultaneously exert a significant impact on buy interest, with the R square of 0.612. This shows that overall, the Trust variables, customer reviews and customer ratings exert significant influences on Buying Interest.